Congenital Anomalies - From the Embryo to the Neonate 2018
DOI: 10.5772/intechopen.73072
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Abnormalities of the Fetal Face

Abstract: Even at the early stages of gestation, the fetal face can be examined. There have been observations of the normal anatomy, such as orbits and the forehead, starting with the 12th week of gestation. However, nowadays, ultrasound equipment still cannot distinguish the soft tissues of the face, which are too thin. Yet, after the age of 14 weeks, we can easily examine the forehead, orbits, nose, lips, and ears. Recently, three-dimensional ultrasound (3D) images of the fetus can also be obtained. However, two-dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Out of 62 articles, eight (13%) articles had a low risk of bias,182–189 45 (72%) articles had some concerns,185 190–234 and nine (15%) articles had a high risk of bias235–243 (figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Out of 62 articles, eight (13%) articles had a low risk of bias,182–189 45 (72%) articles had some concerns,185 190–234 and nine (15%) articles had a high risk of bias235–243 (figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…The overall ratings of the applicability of the articles to the review question found one (2%) article had a high level of concern,241 20 (31%) had some concerns,195 200 205 206 212 214 215 217 220 222 225 226 231–234 237–240 and 41 (67%) had a low level of concern 182–194 196–199 201–204 207–211 213 216 218 219 221 223 224 227–229 235 236 242 243…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations